Folded Cascode Op-Amps – A survey - Anil Sharma (International Journal of Advanced Science and Technology, 2020)
In modern time, CMOS technology has evolved rapidly and has facilitated AMS IC’s to dominate the current market by providing fast frameworks with low supply and low power with reduced dimensions. Operational Amplifier is the most essential structure when AMS integrated circuits are contemplated. Several designs with body driven approach are presented, though this technique has gm low with factor of 4 to 5 than gate driven approach in CMOS. Body driven technique presents various disadvantages of large input capacitance and low trans-conductance (gm) however, the problem of latch up present in gate driven approachiseradicatedinbodydrivenapproach.Thedownsidesofreducedtrans conductance can be reduced with the help of positive partial feedback to improve the trans-conductance and in turn enhances diverse characteristic Op-Amp parameters.